Pengaruh Penyuluhan Asi Eksklusif Pada Bayi Usia 0-6 Bulan Melalui Media Poster Di Puskesmas Pengasinan - Arini, Firlia Ayu; Amalia, Salma Haya; Firlia Ayu Arini; Intania Sofianita; Utami Wahyuningsih (Segara : Jurnal Pengabdian Kepada Masyarakat, 2025)
Breast milk is the best source of nutrition for babies, containing all the nutrients necessary for healthy growth and development. Babies aged 0-6 months are an important period in the First 1000 Days of Life so their growth and development is influenced by good nutritional intake. Exclusive breast milk is the main intake given to babies aged 0-6 months, breast milk contains antibodies for the body's immunity. Low levels of exclusive breastfeeding for babies can affect the nutritional status of babies in the future. So, knowledge is needed for mothers in the form of education regarding the importance of exclusive breastfeeding for babies aged 0-6 months. The aim of this activity is to analyze the coverage of exclusive breastfeeding with factors inhibiting exclusive breastfeeding and increase the knowledge of mothers of babies with intervention in the form of education regarding the importance of exclusive breastfeeding for babies aged 0-6 months in the Pengasinan Community Health Center UPTD working area. Education was carried out using posters for 30 mothers. The results obtained from the Wilcoxon Signed Rank Test are the Sig value. 0.000 < 0.05. The conclusion from the tests carried out was that there was an effect of educational outreach on increasing mothers' knowledge regarding exclusive breastfeeding.